2017
DOI: 10.1111/srt.12361
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐ and inter‐individual variability in the mechanical properties of the human skin from in vivo measurements on 20 volunteers

Abstract: Results: The experimental data obtained are fitted with a phenomenological exponential model allowing the identification of three parameters characteristic of the tested skin behavior. These parameters can be related to the concept of skin extensibility used by surgeons. Conclusion:The inter-and intra-variability observed on that cohort confirms the need for a patient-specific approach based on the in vivo measurement of the mechanical behavior of the human skin of interest. Even the direction of higher skin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…Several skin models have been established for determining the penetration kinetics of drugs into the skin [40]. Due to intra-and inter-individual variability of the skin models, only limited standardized data are available [40,41]. In chronic inflammatory skin diseases, such as atopic dermatitis, the barrier function of the skin is disturbed and thus weakened [42].…”
Section: Discussionmentioning
confidence: 99%
“…Several skin models have been established for determining the penetration kinetics of drugs into the skin [40]. Due to intra-and inter-individual variability of the skin models, only limited standardized data are available [40,41]. In chronic inflammatory skin diseases, such as atopic dermatitis, the barrier function of the skin is disturbed and thus weakened [42].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the biomechanical properties of skin materials revealed that mechanical behavior was closely related to the collagen network of skin [21]. Jacquet et al [22] achieved skin stress-strain curves under di erent conditions by conducting uniaxial tensile tests on volunteers with di erent anatomical locations and di erent directions. Karimi et al [23] obtained the prelinear viscoelastic properties of rat back and abdominal skin under uniaxial loading.…”
Section: Finite Element Analysis Of the V-y Flapmentioning
confidence: 99%
“…As in Jacquet et al (2017a), three physical parameters are identified from the stress-strain curve using a non-linear least squares method:…”
Section: Extensometrymentioning
confidence: 99%
“…One possibility consists in studying keloids by means of measurement devices dedicated to in vivo skin (de Rigal, 2002;Boyer et al, 2013;Dobrev, 2014;Jacquet et al, 2017b). These devices address in different ways the complexity tied to the skin properties -anisotropic viscous, hyperelastic and prestressed tissue (Xu et al, 2008) -and to the variability of the skin as a function of the body site, the age and the posture of individuals (Flynn et al, 2011;Jacquet et al, 2017a). Krusche and Worret (1995) have carried out suction tests on keloids at a macroscopic scale in order to evaluate an antikeloidal treatment.…”
Section: Introductionmentioning
confidence: 99%